Implementasi Low Power Mode Pada Pendeteksi Kebocoran Gas Dengan Atmega328P Berbasis NRF24L01 - Ahmad Fikri Marzuqi; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
LPG (Liquefied Petroleum Gas) is an alternative fuel for petroleum and gas replacement. Gas fuel could explode because of gas leaks, the design of the system of gas leaks detection, is important for minimizing fire of gas leaks. It uses the low power performance with atmega based NRF24L01 for device. The reason of using low power with atmega328p's microcontroller on transmitter node is for saving a power consumption, and also using wireless sensor network based NRF24L01 to minimize cable installation. The method consists of 3 node sensors those are transmitter and 1 receiver node sensor, then it will be linked with personal computer. The result of testing was concluded that the system can work as principle. Transmitter node can detected the presence of gas, some features were turned off from sleep node applied and develop system that comes of external interrupt and then data was submitted by wireless. And the result, average current value of sleep mode is 137,84mA and average current value of normal mode is 157,25mA. And the different between sleep mode and normal mode are 20,59mA.